Phonological processing skills influence text-reading fluency in Russian-speaking adolescents - Tatiana Eremicheva; Yana Nikonova; Svetlana Alexeeva (PLoS ONE, 2025)
It is widely acknowledged that phonological processing skills are crucial for reading acquisition. While most research has focused on examining phonological processing in children, adolescents have remained underexplored. The present study aimed to assess phonological processing (PP) skills in Russian-speaking adolescents using the Changing Sound in Pseudoword test from the Russian Test of Phonological Processing (RuToPP). This test involves multiple linguistic processes in its completion and is considered to be the most difficult from the RuToPP. A total of 161 participants (14–18 y.o.) were involved in the study. First, we calculated percentile-based thresholds, which can be used to indicate the potential risk of phonological processing difficulties in adolescents. Then, we analyzed how PP skills influence word, pseudoword, and text reading fluency. The results revealed that PP skills had a small but significant impact on text reading fluency. No significant effects were observed for word and pseudoword fluency. We speculate that, for adolescents, the ability to manage general cognitive load is more crucial for performing complex reading tasks than the level of basic phonological skills.